![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
3个回答
展开全部
a-c=4(√2-1)……①
b=c……②
a^2=b^2+c^2……③
联立②③式得
a²=2c²
∴a=±√2c
(1)当a=√2c时,代入①式
解得c=4
代入a=√2c可解得a=4√2
∴a=4√2,
b=c=4
(2)当a=-√2c时,代入①式
解得c=-12+8√2
代入a=√2c可解得a=12√2-16
∴a=12√2-16
b=c=-12+8√2
综上,a=4√2,b=c=4
或a=12√2-16,b=c=-12+8√2
b=c……②
a^2=b^2+c^2……③
联立②③式得
a²=2c²
∴a=±√2c
(1)当a=√2c时,代入①式
解得c=4
代入a=√2c可解得a=4√2
∴a=4√2,
b=c=4
(2)当a=-√2c时,代入①式
解得c=-12+8√2
代入a=√2c可解得a=12√2-16
∴a=12√2-16
b=c=-12+8√2
综上,a=4√2,b=c=4
或a=12√2-16,b=c=-12+8√2
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询